Ascending aortic false aneurysm following cannulation for perfusion. Issue 2 (April 1976) - Branchini, B; Zingone, B; Vaccari, M
Abstract : A case of false aneurysm originating from the ascending aortic cannulation site in the absence of mediastinal infection is described. Surgical treatment was carried out by means of limited cardiopulmonary bypass and hypothermic circulatory arrest, but the patient died early in the postoperative period. The technical failures responsible for the unsuccessful outcome are emphasized.